Conservation of DNA Methylation Programming Between Mouse and Human Gametes and Preimplantation Embryos. Issue 3 (1st September 2016) - White, Carlee R.; MacDonald, William A.; Mann, Mellissa R.W.
Abstract: In mice, assisted reproductive technologies (ARTs) applied during gametogenesis and preimplantation development can result in disruption of genomic imprinting. In humans, these technologies and/or subfertility have been linked to perturbations in genomic imprinting. To understand how ARTs and infertility affect DNA methylation, it is important to understand DNA methylation dynamics and the role of regulatory factors at these critical stages. Recent genome studies performed using mouse and human gametes and preimplantation embryos have shed light onto these processes. Here, we comprehensively review the current state of knowledge regarding global and imprinted DNA methylation programming in the mouse and human. Available data highlight striking similarities in mouse and human DNA methylation dynamics during gamete and preimplantation development. Just as fascinating, these studies have revealed sex-, gene-, and allele-specific differences in DNA methylation programming, warranting future investigation to untangle the complex regulation of DNA methylation dynamics during gamete and preimplantation development.